Creation of open educational resources during educational practice by means of cloud technologies - Vladyslav Ye. Velychko; Elena G. Fedorenko; Vladimir N. Soloviev; Ludmila V. Dolins'ka (Academy of Cognitive and Natural Sciences, 2022)
Practical training is an integral part of the professional training of future teachers. During the practical training, trainees not only implement their own theoretical training in practice, but also increase the level of information competence. The rapid use of e-learning resources for distance learning during epidemiological constraints caused by biological threats poses new challenges to education in the availability of e-learning resources. The development of electronic educational resources is a difficult task, one of the ways to solve it is to involve future teachers in this process during the initial practice. The experiment of creating open educational resources by means of cloud technologies during the training practice showed the probability of solving this problem. Restrictions in direct contact between participants in the experiment, both due to epidemiological restrictions and through practical training in various educational institutions, are solved through the use of cloud technologies. The latter provides an opportunity to easily disseminate developed open educational resources and disseminate best practices in creating educational content.